Bitcoin, Economic Freedom, and Underground Economies: A Tax Evasion Nexus - Bhutto, Niaz Ahmed; Nawaz, Allah Ditta; Khan, Shabeer (ETIKONOMI, 2025)
Research Originality: Our research uniquely integrates the dimension of economic freedom to assess its moderating effect on tax evasion in G-7 countries. This study also provides the latest tax evasion estimates in G-7 countries using the currency demand approach to measure the effectiveness of policies employed by the regulators to reduce large numbers of tax evasion. Research Objectives: This study estimates tax evasion in G-7 countries and measures the impact of cryptocurrencies on tax evasion at different levels of economic freedom. Research Method: This study employs the Currency Demand Approach to estimate tax evasion and then utilizes asymmetric/symmetric panel techniques (ARDL/NARDL) to confirm the impact of cryptocurrencies and all indicators of economic freedom on tax evasion. Empirical Results: Our investigation unveils that cryptocurrencies significantly impact tax evasion. This study also finds economic freedom indicators' asymmetric/symmetric impact and confirms the moderating impact. Economic freedom indicators significantly increase/decrease the impact of cryptocurrencies on tax evasion. Implications: Cryptocurrencies may be given due importance while drafting tax-related policies, and policymakers must maintain the optimum levels of economic freedom where cryptocurrencies do not support tax evasion.  JEL Classification: H26, E42, O17, E26, C33